Análise da viabilidade financeira e mercadológica da abertura de uma casa de idosos em Curitiba - Veira, Daniel Marques (2019)
The objective of this research is to analyze the market of Elderly Homes in Curitiba-PR With the increase of elderly in the population, it is necessary to have specific spaces for the elderly, where they can count on specific activities for their age group. That promote socialization, health and well-being. Population aging is growing worldwide. Despite a more present mobility regarding the quality of life, the search for the elderly population in the practice of physical exercises, health problems affect these people every day. The dimensions related to physical, emotional, spiritual, environmental health and the experience of social life based on personal beliefs and values consistent with an emancipatory learning, promoting citizenship and ethics towards the elderly. In this sense, it is justified to choose the theme based on the importance of acting quality and effective public policies as a guarantee of the right to health of the elderly. With this growth trend of the market aimed at the elderly, it is necessary to have specific spaces for this audience, where they can have the main objective quality of life of companies to serve the elderly in nursing homes.